(untitled) (GIST – Education and Learning Research Journal, 2022)
The purpose of this research is to determine the motivation factors of teacher candidates regarding the teaching profession. For this purpose, this study was designed with a cross-sectional scanning model, since the data collection process was carried out in one go. The study group of the research, which was designed with the phenomenology pattern, which is one of the qualitative research methods, consists of 20 teacher candidates studying in various departments of Atatürk University Kazım Karabekir Faculty of Education in the 2021-2022 academic year. The data obtained with the semi-structured interview form were analyzed with the help of content analysis. According to the results of the research, teacher candidates are more positively motivated by internal factors related to the teaching profession. Almost all of the negative motivational factors are exogenous. It is seen that these motivational factors affect the attitudes and perceptions of teacher candidates towards their profession. It can be ensured that competent teachers who are motivated by their work can be trained by increasing the motivational elements that are seen as positive by the novice teachers and by reducing the elements that are seen as negative. In this way, significant gains can be achieved at the point of achieving educational goals.